Samuel Allyne Otis correspondence and notice - Otis, Samuel Allyne, 1740-1814.
Notice (1766 August 26) of a judgment of the Inferior Court of Common Pleas, Suffolk County, Mass., against John Boies, stating an amount to be paid to Otis; ALS (1801 April 28) from Otis to Jacob Read relating to political affairs, especially U.S. relations with France, and complaining about living conditions in the new capital, Washington, D.C.; and ALS (1802 May 12) from Otis to William Hill Wells concerning matters relating to the U.S. Senate.
Typewritten transcript of the letter by Otis to Wells is also available in the Manuscript Reading Room.
Delegate from Massachusetts to U.S. Continental Congress, secretary of the U.S. Senate, businessman, and Massachusetts public official.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Boies, John; Read, Jacob, -- 1752-1816 -- Correspondence; Wells, William Hill, -- 1769-1829 -- Correspondence; Massachusetts. -- Inferior Court of Common Pleas (Suffolk County); United States. -- Congress. -- Senate; Courts -- Massachusetts -- Suffolk County; France -- Foreign relations -- United States; United States -- Foreign relations -- France; United States -- Politics and government -- 1801-1809.; Washington (D.C.) -- History; Businessmen; Delegates, U.S. Continental Congress -- Massachusetts; Public officials -- Massachusetts; Secretaries, U.S. Senate